A green analytical method using polyurethane foam for the extraction and determination of lauryl ether sulfate in personal care hygiene products - Muzel, Felipe R. [UNESP]; Rossini, Eduardo L. [UNESP]; Pezza, Helena R. [UNESP] (Soc Brasileira Quimica, 2022)
A green methodology was developed for the extraction and determination of lauryl ether sulfate in raw materials and commercial liquid soap and shower gel samples. The method avoids the use of organic solvents, offering a simple, cheap, and safe analysis. The methodology is based on the sorption of an ionic pair consisting of a cationic dye and an anionic surfactant onto polyurethane foam. The experimental variables were optimized by chemometry to obtain the conditions that maximized extraction of the ionic pair. Digital imaging and spectrophotometry were used for quantification in the linear concentration range from 10.0 to 100 mg L-1. The limits of detection and quantification were, respectively, 2.71 and 9.28 mg L-1 for digital imaging, and 1.74 and 5.83 mg L-1 for spectrophotometry. The methods showed good results when applied to commercial samples, with recoveries in the range 96.8-103%.
Keywords: Green chemistry; Lauryl ether sulfate; Anionic surfactant; Digital imaging; Spectrophotometry